1992
DOI: 10.1016/0079-6107(92)90023-y
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical aspects of neutron scattering from vibrational modes of proteins

Abstract: This review describes a major portion of the published work on neutron scattering experiments aimed at measuring large scale motions in proteins. The importance of these motions for enzyme function and oxygen transport is indicated. The theory applicable to each type of neuron scattering measurement is given and results are discussed with a view to biological relevance. New experiments are suggested and a comparison of neutron scattering data is made with results from other techniques such as raman scattering,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 110 publications
2
17
0
Order By: Relevance
“…Subsequently, low-frequency modes have been indeed observed by Raman spectroscopy for a number of protein molecules [47,48] and different types of DNA [49][50][51][52]. These observed results have also been further confirmed by the neutron scattering experiments [53].…”
Section: Basic Mechanisms Underlying the Efficacy Of Elf-emf Treatmentssupporting
confidence: 73%
“…Subsequently, low-frequency modes have been indeed observed by Raman spectroscopy for a number of protein molecules [47,48] and different types of DNA [49][50][51][52]. These observed results have also been further confirmed by the neutron scattering experiments [53].…”
Section: Basic Mechanisms Underlying the Efficacy Of Elf-emf Treatmentssupporting
confidence: 73%
“…In this ®eld, computer simulations have always been essential for interpreting the experimental spectra due to the complexity of the systems [1,2]. The prevalent simulation technique has been molecular dynamics (MD) simulation, which calculates the detailed motion of all atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Since the pioneer paper entitled ''The Biological Functions of Low-Frequency Phonons'' (Chou and Chen, 1977) was published in 1977, a series of investigations into biomacromolecules from dynamic point of view have been stimulated. These studies have suggested that low-frequency (or terahertz frequency) collective motions do exist in proteins and DNA that hold a very high potential to reveal the profound dynamic mechanisms of many marvelous biological functions in biological systems (see, e.g., Chou, 1983aChou, , 1983bChou, , 1984aChou, , 1984bChou, , 1984cChou, , 1985Chou, , 1987Chou, , 1989Chou and Mao, 1988;Chou et al, 1981Chou et al, , 1989Chou et al, , 1994Martel, 1992;Sinkala, 2006), and a comprehensive review (Chou, 1988)). Such inferences have been later observed by NMR (Chou et al, 2001), and applied in medical treatments (Gordon, 2007(Gordon, , 2008Madkan et al, 2009).…”
Section: Resultsmentioning
confidence: 98%